1995
DOI: 10.1002/1097-0142(19951001)76:7<1145::aid-cncr2820760708>3.0.co;2-3
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of survival in patients with carcinoma of the gallbladder

Abstract: Background. The role of resectional surgery in patients with advanced stages of gallbladder carcinoma has not been fully defined. It is generally believed that the survival depends on the stage of the disease, rather than on the treatment option. Methods. Seventeen selected risk factors were analyzed using univariate and multivariate analyses to predict survival in 87 patients with gallbladder carcinoma who had undergone some form of surgical treatment. Similarly, a subset of 55 patients with American Joint Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

1997
1997
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(29 citation statements)
references
References 11 publications
1
28
0
Order By: Relevance
“…It was reported that resectional surgery [18], early T-stage [2,19,20], stage of disease [19], highly differentiated cancer [2] papillary adenocarcinoma [20,21], and well-differentiated adenocarcinoma [20,21] were associated with a better survival. On the other hand, age >60 [18] and palpable mass [18] had a negative impact on survival. However, the small number of patients in most of these studies limited their clinical impact on the management of gallbladder cancer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was reported that resectional surgery [18], early T-stage [2,19,20], stage of disease [19], highly differentiated cancer [2] papillary adenocarcinoma [20,21], and well-differentiated adenocarcinoma [20,21] were associated with a better survival. On the other hand, age >60 [18] and palpable mass [18] had a negative impact on survival. However, the small number of patients in most of these studies limited their clinical impact on the management of gallbladder cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, it was reported that resection, compared with bypass surgery, was associated with a better survival in advanced carcinoma of the gallbladder [18]. A better 3-year survival was also demonstrated in stage IV disease without distant metastases or portal vein involvement [36].…”
Section: Discussionmentioning
confidence: 99%
“…If biliary atresia or gastric outlet obstruction are concurrently present, bypass surgery would also improve patient quality of life. Surgeons should therefore decide the optimal treatment modality in view of the patient status involved (43, 44) (Level of evidence 3, Level of recommendation C). Table 7 summarizes the recommendations for palliative surgery in patients who are not indicated for radical surgery.…”
Section: Surgical Treatments For Other Gb Cancer Stagesmentioning
confidence: 99%
“…If the pathology report reveals a Tis or T1 gallbladder cancer, prognosis is good in the case of unviolated gallbladder and negative resection margins. The corresponding 5-year survival rates are 79-100% after simple cholecystectomy [1,6,7,28,29]. However, some authors [30] recommend extended cholecystectomy in the pT1b stage due to suspected venous, lymphatic, or perineural tumor invasion, although lymph node involvement in Tis or T1 tumors is extremely rare [28].…”
Section: Postoperative Morbidity and Mortalitymentioning
confidence: 99%
“…Some authors even advocate nonradical surgery in such cases, as this improves survival compared to only bypass operations [29]. The same authors further recommend the wide use of gastrojejunostomy because of gastric outlet obstruction in one third of the patients submitted to surgery [40].…”
Section: Prognostic Factorsmentioning
confidence: 99%